Noninvasive assessment of portal pressure by combined measurement of volumetric strain and stiffness of in vivo human liver - Jaitner, Noah; Safraou, Yasmine; Anders, Matthias; Schattenfroh, Jakob; Meyer, Tom; Huang, Biru; Jordan, Jakob; Boehm, Oliver; Caiazzo, Alfonso; Schaeffter, Tobias; Mura, Joaquin; Guo, Jing; et al. (Acta Biomaterialia, 2025)
Liver metabolism depends on the mechanical interplay between the solid tissue matrix and blood vessels, making shear modulus and pressure important variables of hepatic homeostasis. While shear modulus can be quantified by magnetic resonance elastography (MRE), pressure is not available through noninvasive imaging. We propose combined determination of liver deformation and shear modulus using volumetric MRI and MRE for noninvasive portal pressure assessment. Volumetric MRI and multifrequency MRE were performed in five ex vivo rat livers at different portal pressures. A similar imaging protocol was used to examine eleven healthy volunteers after overnight fasting in two respiratory states and after ingestion of 1.5 L of water. Models derived from ex vivo rat data served to scale human liver volumetric strain multiplied by differential shear modulus obtained from MRE to portal pressure. After water intake, liver volume expanded by 3 % (Interquartile range [IQR], 1.3–6.0; p < 0.001) and shear modulus increased by 0.12 kPa (IQR, 0.08–0.26; p = 0.001), while deep inhalation had mixed effects (p > 0.05). Positive and negative volumetric strains were associated with stiffening and softening, respectively, leading to a consistent increase in portal pressure of 0.2 to 0.3 kPa (IQR, 0.07–0.41) for inhalation and water ingestion. In conclusion, volumetric strain analysis combined with MRE in different scenarios of in vivo liver deformation and calibration with controlled ex vivo experiments allowed assessment of portal pressure changes. In clinical applications, combined MRE and volumetric MRI after inspiration or water ingestion could provide mechanical contrast for assessing hepatic pressure-related diseases. Statement of significance: Using 3D MRI and MR elastography, this study introduces trained image segmentation and registration based quantification of liver volumetric strain in combination with shear modulus measurement for non invasive assessment of portal venous pressure. Volumetric strain and tissue stiffening due to altered portal venous pressure are quantified in ex vivo rat livers and under physiological conditions in healthy volunteers. It is shown that the new method is sensitive to subtle changes in in vivo portal pressure in the range of 0.2 to 0.3 kPa due to deep inspiration or water intake. Our method offers a diagnostic tool for liver pressure related diseases by providing a better understanding of the liver shear modulus and its relationship to portal venous pressure.
Created from Fastlane, Scopus look-up
Keywords: Deformation field; Deformation mapping; Hepatic pressure; Image registration; Liver; Magnetic resonance elastography (MRE); Octahedral shear strain (OSS); Portal pressure; Segmentation; Stiffness; U-Net; Volumetric magnetic resonance imaging (MRI); Volumetric strain